Highly efficient access to well-defined linear polymers with substantial vinyl pendants via ATRP of divinyl monomers. Issue 32 (31st July 2018) - Wang, Xiao-Yan; Sun, Xiu-Li; Chen, Zhi-Hao; Wang, Feng; Wang, Sunewang R.; Tang, Yong
Abstract : Reported herein is a highly efficient access to well-defined linear polymers with substantial vinyl pendants via ATRP of dissymmetric divinyl monomers by side armed bisoxazoline (SaBOX)/copper catalysts. Abstract : Reported herein is a highly efficient access to well-defined linear polymers with substantial vinyl pendants via activators generated by electron transfer (AGET) atom transfer radical polymerization (ATRP) of dissymmetric divinyl monomers by side armed bisoxazoline (SaBOX)/copper catalysts. High conversions (>90%) of the divinyl monomers allyl methacrylate (AMA) and vinyl methacrylate (VMA) without gelation through ATRP were realized with a relatively high concentration ratio of monomer to initiator in feed ([M]0 /[I]0 ≥ 100), yielding completely soluble homopolymers with relatively high molecular weights and narrow molecular weight distributions ( M n 's = 1.49–3.69 × 10 4, Đ 's = 1.2–2.0). Besides, random MMA copolymers with different amounts of pendant vinyl groups (18–54 mol%) were conveniently obtained by employing AMA or VMA as the comonomer.